2021
DOI: 10.26710/jafee.v7i4.2079
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Monetary Policy on Inflation and Investment in Pakistan: A Time Series Analysis

Abstract: Purpose: This study aims to explore the impact of monetary policy on inflation and investment in Pakistan. Methodology: Our study employs the Autoregressive distributed lag model (ARDL) over the time of 1972 to 2019. Findings: The empirical findings show that in the long-run impact of money supply has significant and positive on investment and other variables trade, foreign direct investment, gross domestic saving, services are also positively associated with the investment. While other variables i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…This is especially true in Ethiopia, where the government uses strategies to increase imports during periods of high inflation by either engaging directly in import activities (such as importing sugar, food oil, wheat, and related items) or by creating favorable conditions for the private sector to import the necessary goods, such as by setting up the forex. Likewise, inflation may restrict the volume of goods available for exports by encouraging exporters to sell their goods domestically or by increasing the cost of exportable goods in the international market [ [47] , [48] , [49] ]. This predicament is particularly significant for nations that export basic goods such as food and whose macroeconomic conditions are unstable.…”
Section: The Data and Methodsmentioning
confidence: 99%
“…This is especially true in Ethiopia, where the government uses strategies to increase imports during periods of high inflation by either engaging directly in import activities (such as importing sugar, food oil, wheat, and related items) or by creating favorable conditions for the private sector to import the necessary goods, such as by setting up the forex. Likewise, inflation may restrict the volume of goods available for exports by encouraging exporters to sell their goods domestically or by increasing the cost of exportable goods in the international market [ [47] , [48] , [49] ]. This predicament is particularly significant for nations that export basic goods such as food and whose macroeconomic conditions are unstable.…”
Section: The Data and Methodsmentioning
confidence: 99%
“…Gillani et al, (2021) documented that monetary policy shapes economy by reducing inflation, balancing supply and demand and there by influencing investment in the economy. Chaudhry et al, (2021) found that over long term monetary policy have positive effect on foreign direct investment, savings and investment. Alam and Waheed (2006), examined the impact of monetary policy on different sectors of the economy by using quarterly data spanning from first quarter of 1973 to last quarter of 2003.…”
Section: Literature Reviewmentioning
confidence: 99%